2022
DOI: 10.2514/1.a35030
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Performance Evaluation of Space Radiator for Single-Phase Mechanically Pumped Fluid Loop

Abstract: This paper presents the experimental and analytical results of a heat rejection system consisting of a single-phase mechanically pumped loop and a space radiator. It has been developed for future crewed exploration missions to provide a large amount of heat dissipation capability. The radiator consists of a honeycomb radiator, eight aluminum pipes inserted through the honeycomb core, and two aluminum manifolds joined at both ends of the eight pipes. A graphite sheet is attached to the back of the aluminum skin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…As an important active thermal control technology, a fluid loop system uses the pump to drive the forced fluid-convectioncirculation for temperature control, has been widely applied in many domestic and foreign spacecraft [15][16][17][18]. In order to meet the heat dissipation requirements of this laser mentioned above, the fluid circuit system based on the PEHE is designed, and the composition schematic diagram is shown in figure 2.…”
Section: The Thermal Control Designmentioning
confidence: 99%
“…As an important active thermal control technology, a fluid loop system uses the pump to drive the forced fluid-convectioncirculation for temperature control, has been widely applied in many domestic and foreign spacecraft [15][16][17][18]. In order to meet the heat dissipation requirements of this laser mentioned above, the fluid circuit system based on the PEHE is designed, and the composition schematic diagram is shown in figure 2.…”
Section: The Thermal Control Designmentioning
confidence: 99%
“…Validation of conjugate heat transfer analysis. The experimental results reported by Iwata et al 30 are used to validate the conjugate heat transfer analysis methodology, throughout this section. They reported that the experiments were carried out in a thermo-vacuum chamber, where a pressure of 10 À3 Pa and shroud temperature of 100 K are maintained.…”
Section: Conjugate Heat Transfer Analysismentioning
confidence: 99%
“…Inputs for the validation case. 30 Area of radiating surface 0.648 m 2 Emissivity of radiating surface 0.9 Sink temperature À173°C…”
Section: Conjugate Heat Transfer Analysismentioning
confidence: 99%